IDENTIFICATION OF SALTWATER DISTRIBUTION USING ELECTRICAL RESISTIVITY TOMOGRAPHY IN BANJARSARI, GROBOGAN REGENCY, INDONESIA - Legowo, Budi; Wahyuningsih, Daru; Kurniawan, Muhammad (MATTER: International Journal of Science and Technology, 2018)
Banjarsari village is located to the south of the Bledug Kuwu, the famous of mud volcano in Central Java province. In this location there are surface manifestations such as the mudflow and the saltwater explosion. In this village there are traditional salt mines, therefore a study of the potential source of salt mines is necessary. The aims of this research are detecting and mapping subsurface area of the saltwater intrusion. The direct measurement was conducted using OYO model 2119C resistivitymeter by using Wenner-Schlumberger array configuration and an electrode spacing is 30 meters. The direction of line one (A-A’) and three (C-C’) are from the south tothenorth and line two (B-B’) isthe from east tothewest. Based on the distribution of resistivity, the saltwater with highest salinityindicated have the lowest resistivity (0.020 –0.190 ohm.m). The presence of saltwaterwith highest salinityis expected to be at 30 until 93.8 meters depth. The final result shows that thesaltwater every line has a similar correlation, it means that the saltwater is very wide.